The impact of omnichannel integration towards customer interest in alternatives: retailer uncertainty and web rooming in retailing - Abida Ellahi; Qurat Ul Ain; Hafiz Mudassir Rehman; Md Billal Hossain; Csaba Bálint Illés; Akhtar Tanweer (Cogent Business & Management, 2024)
AbstractThis current study delves into the quality of consumer perception regarding brand channel integration that adopts the omnichannel approach. It specifically explores the impact of process consistency, breadth of the channel service choice, transparency of the channel service configuration, and content consistency, on customers’ inclination towards alternatives. The research incorporates the mediating role of retailer uncertainty and introduces the moderating factor of web-rooming. The analysis, based on data from 319 customers engaged with various omnichannel brands, revealed that the breadth of channel-service choice and process consistency emerged as the most influential factors. These factors contribute significantly to reducing retailer uncertainty and deterring customers from exploring alternative options. The implications of these findings are particularly valuable for industry practitioners, offering insights to shape effective omnichannel business strategies. By prioritizing the breadth of channels and ensuring process consistency, retailers can mitigate uncertainties in customers’ minds, thereby fostering retention and satisfaction.